The Dopamine Transporter in Mesencephalic Cultures Is Refractory to Physiological Changes in Membrane Voltage - Prasad, Balakrishna M. (J Neurosci, 2001)
The dopamine transporter (DAT) plays a crucial role in the clearance of extracellular dopamine in brain. Uptake of dopamine by the cloned human DAT has been shown to be electrogenic and voltage-dependent, with greater uptake observed at hyperpolarized potentials. Ventral mesencephalic dopaminergic neurons were used to assess the kinetics of dopamine uptake in relation to their electrical activity. Dopamine uptake in these cultures was saturable with aK(m) of ∼560 ± 60 nm and a DAT turnover rate of 0.74 ± 0.07 dopamine molecules per second. The effects of physiological changes in membrane voltage on transporter function were assessed by the activation of G-protein-coupled receptors. Current-clamp recordings of dopamine neurons showed that dopamine, baclofen, and orphanin FQ (OFQ) cause varying degrees of hyperpolarization. However, dopamine uptake was not affected by the activation of D(2), GABA(B), or OFQ receptors. Dopamine neurons in culture fired spontaneous action potentials at an average frequency of 2.3 Hz. Thus, dopamine neurons fire approximately three action potentials in the time taken for DAT to go through one transport cycle. Application of tetrodotoxin (1 μm) blocked action potentials but did not alter the uptake of dopamine. These data demonstrate that DAT turnover is a relatively slow process and the rate-limiting step for transport cycle is insensitive to changes in membrane voltage in physiological range.